Manajemen Perawatan Neurointensif pada Miastenia Gravis - Apriansyah Haris Putra, Dicki; Sirin Rifdah S, Lale; Mega Asri D, Putu; Mahfuzzahroni, Muhammad (Jurnal Syntax Fusion, 2021)
Myasthenia gravis (MG) is an autoimmune disorder that affects neuromuscular transmission, causing generalized or localized weakness characterized by fatigue. Myasthenia gravis is most commonly associated with antibodies to the acetylcholine receptor (AChR) on the motor end plate in the postsynaptic neuron. This article aims to determine the appropriate neurointensive management in patients with myasthenia gravis with complications of myasthenic crisis. The writing of this article includes various sources originating from scientific journals and government guidelines and related agencies. Source searches were carried out on online portals for journal publications such as MedScape, Google Scholar (scholar.google.com) and the National Center for Biotechnology Information (ncbi.nlm.nih.gov), with the keyword “Myasthenia Gravis”. The management of myasthenia gravis can be done in various ways, namely, mechanical intubation and ventilation, non-invasive ventilation, pridostigmine as an anticholinesterase inhibitor, immunosuppressant therapy, short term immunotherapy, intravenous immunoglobulin, and surgical therapy. In the treatment of myasthenia gravis, the main goal is to restore muscle condition, especially patient productivity where the management of myasthenia gravis consists of management of myasthenic crisis, cholinergic crisis, symptoms, immunosuppressant therapy, and thymectomy surgical therapy if a tumor is indicated.